GAMBARAN IMPLEMENTASI PENCEGAHAN DAN PENGENDALIAN COVID-19 PADA TUJUH FASILITAS LAYANAN KESEHATAN PROVINSI BENGKULU - Tobing, Vera Tiurma; Modjo, Robiana; Putra, Riskiyana Sukandhi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
As of February 2022, COVID-19 has spread to 227 countries, including Indonesia with 4,516,480 positive confirmed cases where the island of Java is still in the top rank for active COVID-19 cases. Various policies have been implemented by the Government of Indonesia to prevent and control the transmission of COVID-19 by implementing and accelerating vaccinations as well as the imposition of Level 1-4 Restrictions on Community Activities in various parts of Indonesia by taking into account the life and economic factors of the community. This study was carried out to see the fulfillment of health service facilities (hospitals, health centers and laboratories) as workplaces for the implementation of prevention and control of COVID-19 in Bengkulu Province based on KMK No 413 and No 327 of 2020. The study was carried out using a cross sectional survey method, observation, interviews and Focus Group Discussion (FGD) which includes 7 (seven) health service facilities, namely Class B Hospital, Class C Hospital, Outpatient Health Center, Inpatient Health Center and Health Laboratory. From the result of the study, it can be seen that it is still necessary to carry out socialization, continuous improvement as an effort to prevent and control COVID-19 in health care facilities which includes top management commitment, socialization, establishment of systems in health care facilities, application of established systems to periodic evaluations for the continuity of the process so that it is expected to minimize the transmission rate of COVID-19 at the health service facility in particular and the community in general, even in Indonesia. Â  Keyword: Bengkulu, COVID-19, healthcare facilities, Â healthcare workers, control of COVID-19